Delayed migration of Squid 18 following embolisation of a direct carotico-cavernous fistula. Issue 2 (April 2018) - Das, Soumik; Gupta, Arun Kumar; Ramalingiah, Arvinda Hanumathapura; Tiwari, Sarbesh; Yadav, Nishtha
We report a case of delayed migration of Squid 18 following treatment of a direct carotico-cavernous fistula.